The Hill-Korwa - Deogaonkar, S. G. (New Delhi : Concept Pub. Co., 1986)
About the Korwa, Indic people, from Raigarh District in Madhya Pradesh.
Includes index.
Bibliography: p. [82]
mizan
Keywords: Korwa (Indic people); Raigarh (India : District) -- Social life and customs